Gandhi and Sardar : The Ironman of India - problems in the representation of history in historical epics / Wan Aida Wan Yahaya - Wan Yahaya, Wan Aida (UPENA, 2007)
This essay aims to compare and contrast two films that deal with India's struggle for Independence - Richard Attenborough's Gandhi (1982) and Sardar: The Ironman of India (1993, directed by Ketan Mehta). Both of these films were inspired by the remarkable leaders in Indian history who led India to its independence in 1947, Mohandas K. Gandhi and Vallabhbhai Patel. This essay will go on to explore as to whether Gandhi fulfills various cultural associations necessary in representing the history of a different nation and culture, considering its director and scriptwriter are British, their point-of-view would have been that of an outsider or observer. On the other hand, Sardar which was directed by an Indian director who had personal insight into the beliefs and cultural practices of the Indian people presents a more cultural and textured scenario. Whilst examining problems in the representation of history in these two historical epics, this essay also concludes by indicating that the two films not just draw attention to the contribution to the lives and contributions of the two national leaders, but also question the impacts that these leaders had on the nation's history.